Development of Regional Innovative Clusters and Supply Chain Strategy in Terms of Lean Production Principles - Alvina Tarielovna Shilkina; Lyudmila Alexandrovna Fedoskina; Lyudmila Ivanovna Biryukova; Yury Viktorovich Yamashkin; Irina Viktorovna Philippova (International Journal of Supply Chain Management, 2019)
The article considers the genesis, content and relevance of the cluster approach in socio-economic regional development. Certain aspects of the innovativeness of this approach have been discussed in a number of national strategic documents since 2008. In our opinion, their further development and updating is relevant for the upcoming international forum, â€œPartnership for Cluster development: Creating the future,â€ which will be held in the Republic of Tatarstan in 2020. The key goal as part of the development of regional innovative clusters is the development of effective intra-cluster interaction to increase labor productivity. The authors introduce the hypothesis regarding the increase of production systems' efficiency. The necessity of implementing the lean production concept according to the certain cluster model is identified and justified. In relation to this, the conditions and possibilities of having a synergies-tic effect on the joint, interconnected and mutually reinforcing use of lean principles are analyzed. In addition, the model that is implemented by all the participants in the innovative cluster in the product value chain is developed. The authors refer to provisions in international and domestic documents on the sphere of cluster development, recommendations from the national standard GOST R 57524-2017 â€œLean production. Value Stream,â€ methods for calculating process performance indicators, product stocks in buffers, and cycle time of the reverse processes. According to the results of the study, it was concluded that the implementation of lean production principles for the development of innovative regional clusters is universal and effective. Moreover, it has a high degree of feasibility for any organizational model of a cluster. There is scientific and practical interest in the implementation of the entire complex of lean principles to provide for the quality of products and processes, as well as their continuous improvement.